Interaksi Sosial Ekonomi Cacat Netra di Panti Pijat Bagas Waras Papringan Yogyakarta - Rahman, Mahyuzar (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2006)
This research highlights three disabled (blind) people in the term of their ways in dealing with their shortcoming in earning their livelihood and the way they interact with their surrounding, socio-economically and socio-religiously. It is found that they have the ability to meet they daily needs by